Bidentate aliphatic quaternary ammonium ligand-stabilized CsPbBr3 perovskite nanocrystals with high PLQY (92.3%) and superior stability. Issue 21 (18th May 2022) - Li, Ye; Cai, Miaoling; Shen, Mengling; Cai, Yuting; Xie, Rong-Jun
Abstract : A new bidentate ligand strategy was employed to prepare CsPbBr3 NCs, where the DTDB ligand can be tightly anchored to the surface of the NCs with the double N + sites. The as-synthesized DTDB-CsPbBr3 NCs show superior purification endurance and thermal stability. Abstract : The stability of perovskite nanocrystals (NCs) is greatly limited due to highly dynamic binding of ligands, which hinders their applications in optoelectronic devices. In this paper, a new ligand strategy was employed to prepare CsPbBr3 NCs via a facile room temperature (RT) ligand-assisted reprecipitation (LARP) method, where N1.N2-didodecyl-N1.N1.N2.N2-tetramethylethane-1.2-diaminium bromide (DTDB) as the sole capping ligand and an additional Br resource was used. Compared to other ligands with one coordinating group, this class of bidentate ligand can be tightly anchored to the surface of NCs with double N + sites. The as-synthesized DTDB-CsPbBr3 NCs exhibited a high photoluminescence quantum yield (PLQY) of 92.3% and also showed a superior colloidal stability even under intense purification for up to ten cycles. Compared to the dodecyltrimethyl ammonium bromide (DTAB) ligand capped-CsPbBr3 NCs, the DTDB-CsPbBr3 NCs display obviously enhanced stability to light, heat and water. X-ray photoelectron spectroscopy (XPS) results revealed that the DTDB-CsPbBr3 NCs have a Br − rich surface, which accounts for the high stability and PLQY. Hence, DTDB is a promising ligand to prepare perovskite NCs with higher optical performance.